Uso da torta de mamona não destoxificada na indução da muda forçada em poedeiras comerciais - Mucida, Kelliani de Sousa Magalhães (2011)
This study aimed to evaluate the effects of changing diets containing different levels of non-detoxified castor bean meal (TM) in the induction of molt and compare them with the method of fasting. Used 120 Lohman LSL strain hens at 81 weeks of age were assigned to completely randomized design with four treatments and five replicates of six birds each. Treatments were the induction of molt by the method of fasting as a treatment, and others using diets change, being composed of approach ration containing castor bean at levels of 20, 30 and 40% (T2, T3 and T4 ). The method was applied to fast for 11 days and the other treatments, was established to suspend the declaration of change when the birds reached 23% loss of initial weight or up to 21 days supply. Blood samples were collected, one bird per replicate / treatment at the end of induction of changes were analyzed. Significant differences were observed between the methods of molt induction to the parameters measured during the induction of changes in performance of birds after molting. However, the quality of the eggs did not vary significantly among the evaluated methods. In general, the use of feed containing 40% of changes of TM enabled to obtain similar results in the production and egg quality to those obtained with the method of fasting, but with less alteration of blood parameters. The use of feed containing 20% or 30% of TM promoted in the period after the changes, performed significantly lower than other methods. The ration of changes made by laying diet containing not detoxified castor bean meal in the level of 40% proved to be a viable alternative to using the method of fasting.